The Intelligence of Dogs - Coren, Stanley (London Pocket Books, 2006)
How Smart Is Your Dog? If you've ever wondered what is really going on inside your dog's head, here is your chance to find out. In this revised and updated version of this perennially popular book, psychologist and prizewinning trainer Stanley Coren provides a startling view of the intelligence of our oldest and closest animal companions. Do dogs really think? Are they conscious in the same way humans are? What is the nature of canine memory? Can dogs communicate with us -- and, if so, how can we understand them? Do they have feelings such as guilt, loyalty, and jealousy? Do they experience joy and sorrow? Drawing on scientific research that has stood the test of the past decade, interviews with top breeders and trainers, and his own personal observations as a lifelong dog lover, Stanley Coren speculates on these and many other fascinating questions about man's best friend. He offers practical tips on how to evaluate your dog's body language and understand the sophisticated "language" of a dog's bark, and how to tailor a training program to suit your dog's special needs. Here, too, are the famous, controversial lists and rankings of more than 100 breeds for obedience and working intelligence, as well as for specialized tasks such as hunting, home security, and companionship. Rich in wit, wisdom, and anecdote, "The Intelligence of Dogs" is a book that will bring you a greater understanding and enjoyment of the habits, antics, and abilities of your dog.
Keywords: Applied Sciences